Main Principles of Formation of the Complex of Models of Management of Financial Risks of a Company Основные принципы формирования комплекса моделей управления финансовыми рисками предприятия - Polyakova Olga Yu.; Goltyaeva Lyudmila A. (Bìznes Inform, 2013)
The article is devoted to basics of management of financial risks of a company. It develops a system of management of financial risks of a company and identifies main principles of its construction. It provides tasks, goals, methods and purpose of a complex of economic and mathematical models of management of financial risks of a company. Статья посвящена основам управления финансовыми рисками предприятия. В ходе исследования разработана система управления финансовыми рисками предприятия, определены основные принципы ее построения. Представлены задачи, цели, методы и назначение комплекса экономико-математических моделей управления финансовыми рисками предприятия.